Corrective and Preventive Actions of Pharmacist Preceptor in Guiding Pharmacy Internship at Public Health Center during the COVID-19 Pandemic - Nirma Atin Shintia; Yosef Wijoyo (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
During the COVID-19 pandemic, a pharmacy internship at the Public Health Centers (PHC) was carried out by complying with the implementation of health protocols. There were risks for students to be exposed to COVID-19 when a pharmacy internship was carried out directly at the PHC, and some pharmacy internship materials could not be applied easily due to the pandemic. This study aimed to identify the corrective and preventive actions of the preceptor in guiding the pharmacy internship at the PHC during the COVID-19 pandemic. This descriptive study was conducted using the in-depth interview method and examined using qualitative data analysis. The results of interviews were categorized into six issues, namely: 1) roles and abilities as preceptors; 2) pharmacy college institution support; 3) pharmacy internship mentoring methods; 4) corrective and preventive actions to overcome problems in pharmacy internships during pandemics; 5) pharmacy internship modules; and 6) barriers and factors supporting the role of preceptors. Preventive action taken by the preceptor was generally in relation to government policies during the pandemic and infection prevention and control programs in PHC. Concurrently, the corrective actions were modifying learning methods and using information technology to support pharmacy internship learning outcomes during the pandemic and post-pandemic.